In vitro Cytotoxic, Antioxidant and Antimicrobial Activities of Alcoholic and Chloroform Extracts of Dhofari Frankincense (Dhaka University Journal of Pharmaceutical Sciences, 2020)
Omani (Dhofari) frankincense is world famous for its high quality and fragrance. The oleo-gum resin obtained from the tree of Omani species i.e., Boswellia sacra (local name: luban) is widely used by the natives. The aim of the study was to determine the presence of phytochemicals in chloroform and ethanol extracts of B. sacra resin and to evaluate the in vitro cytotoxic, antimicrobial- and antioxidant-activities. The ethanol and chloroform extracts of Hojari luban were obtained in good yield. The extracts were subjected to phytochemical screenings, quantification of total phenolics (TP) and evaluation of in vitro biological activities viz. antioxidant, antibacterial and cytotoxic potential. The bioactivities of four boswellic acids, the major constituents of the oleo-gum resin, were also predicted with the help of PASS and CLC-pred software. Both the extracts showed similar level of TP (14.67 mg/g and 14.79 mg/g in terms of gallic acid equivalent) but polar fraction was noted to be more active against E. coli. A moderate antioxidant activity was shown by the resin extracts however their cytotoxic activity was observed to be quite remarkable at 1000 μg/l which could be attributed to their high boswellic acid content. Results of in silico PASS studies showed boswellic acids to possess an array of useful biological activities including chemopreventive activity. Further, CLC-pred software revealed that only keto boswellic acid is expected to exert antineoplastic activity against pancreatic carcinoma cell lines, however all the four major boswellic acids are likely to be active against non-tumor embryonic lung fibroblast (MRC5). The study confirmed that frankincense is rich in bioactive metabolites which are of significant economic and therapeutic importance.Dhaka Univ. J. Pharm. Sci. 19(2): 105-110, 2020 (December)